Desain Sistem Informasi Akuntansi Sebagai Upaya Peningkatan Kualitas Pencatatan Keuangan pada UMKM Pabrik Permen Lolipop Barokah - Faradila, Vahma; Indrawan, Andi Kusuma; Nurfitriasih, Dyah Metha (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2025)
The study aimed to design and implement an Accounting Information System (AIS) for the MSME "Pabrik Permen Lolipop Barokah" and to analyze its financial performance based on the financial statements generated by the system. The AIS was developed in accordance with the operational needs of the business and the applicable standard, namely the Financial Accounting Standards for Micro, Small, and Medium-sized Entities (SAK EMKM - Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah). This study was an applied case study with a qualitative descriptive approach. Data were collected from both primary and secondary sources through observation, interviews, and documentation. The system was developed using Microsoft Excel, enhanced with macro features to support process automation. The results of the study showed that the designed AIS successfully supported the systematic recording of sales, purchases, inventory management, and the preparation of key financial statements. The system was found to be both effective and user-friendly, particularly for users with limited accounting knowledge. Furthermore, the results of financial ratio analysis revealed that the MSME’s financial performance was in the fairly good category, especially in terms of liquidity and profitability. Overall, the implementation of the system contributed not only to improving financial recording practices but also to supporting better decision-making for small businesses.